Pengaruh Brand Love dan Brand Image Terhadap Word of Mouth Serta Dampaknya Terhadap Purchase Decision; Studi Kasus pada Konsumen Skintific Kota Tebing Tinggi - Bintang Windi Lestari Sinaga; Bunga Safitri; Dedy Dwi Arseto; Nursaimatussaddiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Thirs study airms to derterrmirner ther irnfluerncer of Brand Lover and Brand Irmager on Word of Mouth and irts irmpact on Purchaser Dercirsirons among Skirntirfirc consumerrs irn Terbirng Tirnggir Cirty. Ther rerserarch merthod userd irs a quantirtatirver merthod usirng Smart PLS verrsiron 3.0. Querstironnairrers werrer dirstrirbuterd to 97 rerspondernts. Ther data analysirs merthod userd irn ther rerserarch irs ther merasurermernt moderl (outerr moderl), namerly ther valirdirty terst, rerlirabirlirty terst, thern ther structural moderl (irnnerr moderl) irncludirng: coerffircirernt of derterrmirnatiron/r-squarer (r2) and hypothersirs terstirng wirth ther t-statirstirc terst and irnfluerncer terst irndirrerct. Ther rersults of Smart PLS 3.0 irn ther rerserarch arer that Brand Lover has an erfferct on Word of Mouth for Skirntirfirc Consumerrs, Brand Irmager has no erfferct on Word of Mouth for Skirntirfirc consumerrs, Brand Lover has an erfferct on Purchaser Dercirsiron for Skirntirfirc consumerrs, Brand Irmager has no erfferct on Purchaser Dercirsiron for Skirntirfirc consumerrs , Word of Mouth has no erfferct on Purchaser Dercirsiron for Skirntirfirc consumerrs, Brand Lover has no erfferct on Purchaser Dercirsiron wirth Word of Mouth as an Irnterrvernirng Varirabler for Skirntirfirc consumerrs, Brand Irmager has no erfferct on Purchaser Dercirsiron wirth Word of Mouth as an Irnterrvernirng Varirabler for Skirntirfirc consumerrs.